Amino acid sensing and mTOR regulation: inside or out? - Goberdhan, D; Ogmundsdóttir, M; Kazi, S; Reynolds, B; Visvalingam, S; Wilson, C; Boyd, C (2009)
mTOR (mammalian target of rapamycin) plays a key role in determining how growth factor, nutrient and oxygen levels modulate intracellular events critical for the viability and growth of the cell. This is reflected in the impact of aberrant mTOR signalling on a number of major human diseases and has helped to drive research to understand how TOR (target of rapamycin) is itself regulated. While it is clear that amino acids can affect TOR signalling, how these molecules are sensed by TOR remains controversial, perhaps because cells use different mechanisms as environmental conditions change. Even the question of whether they have an effect inside the cell or at its surface remains unresolved. The present review summarizes current ideas and suggests ways in which some of the models proposed might be unified to produce an amino acid detection system that can adapt to environmental change.